Hydrogen sulfide action in the regulation of plant autophagy. Issue 17 (3rd July 2022) - Aroca, Angeles; Gotor, Cecilia
Abstract : Hydrogen sulfide is a signalling molecule with a well‐established impact on both plant and animal physiology. Intense investigation into the regulation of autophagy by sulfide in Arabidopsis thaliana has revealed that the post‐translational modification of persulfidation/S‐sulfhydration plays a key role. In this review focused on plants, we discuss the nature of the sulfide molecule involved in the regulation of autophagy, the final outcome of this modification and the persulfidated autophagy proteins identified so far. A detailed outline of the actual knowledge of the regulation mechanism of the autophagy‐related proteins ATG4a and ATG18a from Arabidopsis by sulfide is also included. This information will be instrumental for furthering research on the regulation of autophagy by sulfide. Abstract : Hydrogen sulfide (H2 S) is a signalling molecule with a well‐established impact on both plant and animal physiology. Here, we discuss the regulation of plant autophagy by H2 S, the persulfidated autophagy proteins identified so far and the final outcome of this modification.